Comparison of procedural characteristics of percutaneous annuloplasty and edge-to-edge repair for the treatment of severe tricuspid regurgitation - Mattig, Isabel; Barbieri, Fabian; Kasner, Mario; Romero Dorta, Elena; Heinrich-Schüler, Anna Lisa; Zhu, Miry; Stangl, Karl; Landmesser, Ulf; Reinthaler, Markus; Dreger, Henryk (Frontiers in Cardiovascular Medicine, 2023)
Background: In recent years, new interventional therapies for tricuspid regurgitation (TR) demonstrated their effectiveness in reducing TR severity and improving symptoms. Currently, tricuspid transcatheter edge-to-edge repair (T-TEER) and percutaneous annuloplasty are the most widely used techniques in Europe. In this retrospective study, we compared procedural characteristics and learning curves of both TR devices in a real-world cohort. Material and methods: Eligible patients with severe to torrential TR underwent either percutaneous annuloplasty or T-TEER as recommended by the local heart team. Patients with combined mitral and tricuspid interventions were excluded from the analysis. The study focused on procedural characteristics, TR reduction and learning curves. Results: A total of 122 patients underwent either percutaneous annuloplasty (n=64) or T-TEER (n=58) with a technical and device success rate of 98% and 97%, respectively. Reasons for technical failure included right coronary artery (RCA) dissection prior to percutaneous annuloplasty, and two single leaflet device attachments (SLDA) during T-TEER implantation. The mean improvement of TR severity was 2.4±0.8 degrees after T-TEER and 2.5±0.8 after percutaneous annuloplasty. T-TEER procedures were shorter in terms of both procedure time and radiation exposure, while percutaneous annuloplasty, although taking longer, showed a significant reduction in procedure time over the course of the analysed period.In summary, both interventional therapies reduce TR severity by approximately two degrees when used in the appropriate anatomy. The learning curve for annuloplasty group showed a significant decrease of procedure times.